Worsening Of Existing And New Onset Headaches Associated With Face Masks Among Healthcare Professionals - Ishaq, Ayesha; Mahmood, Riaz; Nasir, Sadaf; Mujtaba, Ghulam; Ghazala, Shakeela; Anwar, Hamza (Journal of Rawalpindi Medical College, 2025)
Objective: This study aims to investigate the frequency of protective facemask-associated headache disorders among Pakistani doctors in terms of new-onset and exacerbation of existing headache disorders Methodology: A cross-sectional survey was designed to get data from medical doctors working at tertiary care hospitals of Islamabad/Rawalpindi from November 2023 to June 2024 after the hospital’s ethical committee approval. The online survey was designed as a specifically developed questionnaire, and it was distributed in the form of a Google form link to various medical doctors working in tertiary care hospitals of Islamabad/Rawalpindi until the sample of 300 medical doctors was achieved. Some doctors were approached personally as per convenience and their responses were noted after informed consent. Results: The mean age of study participants was 29.78±4.31 years, with 128 (42.7%) males and 172 (57.3%) females. 33.0% of medical doctors reported having a history of previous headaches, while 48 (16.0%) developed a new onset of headache. A significantly higher number of participants who had migraine headaches reported experiencing an increase in the frequency of their headache as compared to those with history of tension-type headache or cluster headache (52.3% vs 34.1% vs 13.6% respectively, p=0.017) and increased severity of their headache as compared to those with history of tension-type headache or cluster headache (54.8% vs 35.7% vs 9.5% respectively, p=0.003). About 83 out of 147 (56.5%) reported that they had noticed improvements in headaches after taking off the facemasks. Conclusion: It can be concluded that there is a significant relationship between facemask use and the worsening of existing headaches and also onset of new headache episodes among medical doctors who use PPE for prolonged periods during clinical practice. Keywords: Headache, Masks, Migraine Disorders, Personal Protective Equipment